RUPTURES, DISSENT AND CANCELLATION: STUDIES ON DIGITAL FANDOMS IN CRISIS - F. K. Svegaard, Sebastian; Vilkins, Samantha; FitzGerald, Katherine M.; Amaral, Adriana; Mendonça Caetano, Stella; Santos Vieira, Eloy; Amado Nunes Costa, Aianne; Govari Nunes, Caroline; Driessen, Simone; Jones, Bethan (AoIR Selected Papers of Internet Research, 2026)
Scholars working across fan studies, internet studies and politics have noted the increasing use of cancellation practices across media, politics and culture and within digital spaces. Cancel culture is “the withdrawal of any kind of support (viewership, social media follows, purchases of products endorsed by the person, etc.) for those who are assessed to have said or done something unacceptable or highly problematic, generally from a social justice perspective especially alert to sexism, heterosexism, homophobia, racism, bullying, and related issues” (Ng 2020, 623). Cancellation practices might include unfollowing a creator on social media, refusing to buy books or stream films, or boycotting places. Cancelling has its origins in queer Black communities where marginalized groups engaged in “networked framing” (Clark, 2020), discussing the behaviour of the offending party and “prescrib[ing]d a remedy—such as being fired or choosing to resign—through the collective reasoning of culturally aligned online crowds” (ibid, 89). Yet cancel culture has moved beyond the realm of Black Twitter to enable all marginalised voices to discuss, critique and demand accountability: the 2017 #MeToo-movement highlighted this as scores of women took to social media to expose the extent of sexual harassment and assault in Hollywood, “turbocharged cancel culture” (Ng 2020, 623). Cancel culture has been framed as a form of activism, an activity which has also been linked to fan communities (Jenkins and Shresthova, 2012). Many fans are aware of social inequalities, being members of communities beyond their fandoms which are marginalised by virtue of gender, race or class (Maher, 2020). It is not surprising that fans engage in virtual and physical activism, including charity fundraising, political participation and, increasingly, cancellation. Yet, as Stanfill (2019) points out, cancellation practices can move into the realm of toxic fandom, or even be co-opted by the alt-right as counter-culture (Jurg et al., 2024). To understand these more ambivalent forms of cancel culture we bring together different manifestations and cases of cancellation across the globe. The panel begins with Paper 1, offering an analysis of the various fan - and anti-fan - factions within Taylor Swift fandom, focusing on her relationship with NFL star Travis Kelce. Through issue mapping, network analysis and qualitative reading of a subset of Reddit posts, the authors examine the ways in which fandom, politics, and anti-fandom clash, driven by politically charged concerns and the gendered nature of Swift and Kelce’s respective celebrity status. Music fandom is also the focus of the second paper, in which the authors examine the case of Brandon Pybos, vocalist of the goth band Sonsombre. Analysing fan comments on Facebook the authors identify three main categories: 1) Racism/Racist/Racism as Fascism; 2) Questioning Cancel Culture; and 3) “Fan Pedagogies” and argue that Pybos was ultimately cancelled by fans whose cancelling practices were used as a means of ideological preservation of the subculture. The third paper in this panel moves beyond Western fandom to consider the cancellation of Spanish actress Karla Sofia Gascón by Brazilian fans and haters, articulating aspects of fan studies (toxic fandom, transcultural fandom and other base concepts), cancel culture, pop culture, polarization, and politics in regard to Brazilian fans’ specificities, particularly their ability to manage online mobilizations and conjectures about media phenomena. The final two papers in the panel consider the negation of - or opposition to - cancel culture and cancelling practices. Paper four focuses on female fans of Backstreet Boy Nick Carter who support the singer despite sexual assault allegations being made against him. The author analyses 452 comments posted to a Change.org petition opposing the cancellation of the 2022 ABC Backstreet Boys Holiday Special and identifies three patterns of support for Carter: 1) an ‘innocent until proven guilty’ discourse; 2) perceptions of Carter as a family man, a loving husband, and father, underscored by his social media presence; and 3) believability, in which fans contest the believability of the accusers by digging up digital evidence that disproves their claims. Carter’s thirty-year (parasocial) relationship with his fans provides a support group ready to defend the singer and contest the believability of his accusers. The fifth contribution to the panel examines the ways in which practices of cancel culture are co-opted by the right-wing and reframed as counter-culture. Using Russell Brand as a case study the author analyses Brand’s TikTok and YouTube videos and comments left on them by fans to suggest that attitudes to and perceptions of cancel culture are changing as a result the rise of new platforms and the ‘saleable commodity’ that a contradictory, right-wing position is now becoming. Overall, this panel brings together interdisciplinary and global case studies which critically discuss the relationship between fandom, activism, cancellation and polarisation across a variety of genres and countries. It offers timely and relevant insights into today’s online media landscape by highlighting fannish practices with real-world consequences.